2016
DOI: 10.5489/cuaj.3163
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of time to biochemical recurrence in a radical prostatectomy cohort within the PSA-era

Abstract: Introduction: We sought to determine predictors for early and late biochemical recurrence following radical prostatectomy among localized prostate cancer patients. Methods: The study included localized prostate cancer patients treated with radical prostatectomy (RP) at the University of Southern California from 1988 to 2008. Competing risks regression models were used to determine risk factors associated with earlier or late biochemical recurrence, defined using the median time to biochemical recurrence in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The amount of progressive cancers in the prostatectomy tumor sets were the same (60.0% screening set and 61.0% validation set), but the median onset of progression was two times shorter in the screening set (2.1 years) compared with the validation set (4.2 years). Although no statistically significant difference was detected between the sample sets, the median onset time in the screening set can be classified as an early biochemical recurrence and the median onset time in the validation set as a late biochemical recurrence based on a cutoff point 2.91 years, which has been used by others (Shahabi et al, ). The observed tendency toward shorter progression onset in the tumor set of the screening analysis might be a confounding factor since DGAT2 expression has been observed to be positively associated with a biochemical recurrence (Heemers et al, ), but this finding is not related to the SNPs studied here, because the SNPs are not associated with a PSA progression (Nurminen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of progressive cancers in the prostatectomy tumor sets were the same (60.0% screening set and 61.0% validation set), but the median onset of progression was two times shorter in the screening set (2.1 years) compared with the validation set (4.2 years). Although no statistically significant difference was detected between the sample sets, the median onset time in the screening set can be classified as an early biochemical recurrence and the median onset time in the validation set as a late biochemical recurrence based on a cutoff point 2.91 years, which has been used by others (Shahabi et al, ). The observed tendency toward shorter progression onset in the tumor set of the screening analysis might be a confounding factor since DGAT2 expression has been observed to be positively associated with a biochemical recurrence (Heemers et al, ), but this finding is not related to the SNPs studied here, because the SNPs are not associated with a PSA progression (Nurminen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical recurrence (BCR) occurs in 8‐30% of patients within 10 years of radical prostatectomy (RP) and in some, BCR heralds rapid and aggressive disease, while in others the natural history might be indolent . Moreover, recent studies found similar survival rates for patients with and without BCR at 10 years after RP and the 15‐year probability of death from prostate cancer (PCSM) versus other causes seems to be comparable for patients in both groups .…”
Section: Introductionmentioning
confidence: 99%
“…Shahabi et al have searched risk factors for biochemical relapse in 2262 RP patients. These patients had not received any neoadjuvant or adjuvant treatment (pT2-3N0M0) [20]. In this study, they accepted the first 35 months after RP as early relapse and more than 35 months as late relapse.…”
Section: Discussionmentioning
confidence: 99%